Individual empowerment and community norm effects of engaging young husbands in reproductive health in rural India: findings from a pilot study - Nadia Diamond-Smith; Yogesh Vaishnav; Usha Choudhary; Payal Sharma; Ankur Kachhwaha; Tamera Panjalingam; Janelli Vallin; Debangana Das; Lakshmi Gopalakrishnan (Reproductive Health, 2024)
Abstract Background Despite decades of a call to action to engage men in reproductive health, men are often left out of programs and interventions. In India, where half of pregnancies are reported as unintended, patriarchal gender norms and still dominant patterns of arranged marriages make engaging men in family planning and strengthening couples communication critical in increasing reproductive autonomy and helping young couples meet their reproductive goals. This study explores the feasibility and acceptability from the men’s perspective of the pilot of a gender transformative intervention for newly married couples in India. Methods A pilot study was conducted of TARANG, a 4 month intervention for newly married women, with light touch engagement of husbands (4 sessions). A total of 41 husbands participated in the pilot, and we collected baseline knowledge and endline feasibility and acceptability data from them, along with in depth qualitative interviews with 13 men. The study was conducted in June 2023-January 2024. Results Men had low levels of knowledge about biology, family planning, with the majority of men reporting that no one had provided them information about these topics. Most men wanted to delay the first birth by at least 2 years, yet less than a quarter had discussed childbearing plans with their partner or engaged in family planning methods. While all men reported high acceptability (satisfaction and usefulness), feasibility (participation) was low, with only 43% attending 2 or more sessions. Main barriers to participation included commitments due to work and migration. Men reported that the intervention led to improvements in their relationships with their wives, gave them a sense of empowerment, and led them to become resources for other men in their community. Conclusions Men in these rural communities are not receiving the information that they need to meet their reproductive goals, however, they greatly desire this information and ways to improve relationships with their new wives. Such an intervention appears to have the potential to help change norms and spread information in the community and provide men with positive, life affirming feelings. Providing information through technology could address barriers to in-person engagement. Trial registration clinicaltrials.gov  03/13/24.NCT06320964